The impact of MicroRNA-155 on the effect of cryoablation in paroxysmal atrial fibrillation: MicroRNA-155 in cryoablation for atrial fibrillation - He, Wangwei; Tang, Rong; Han, Junyu; Zhang, Ziguan; Li, Jun; Xue, Wanwan; Xie, Qiang (Cellular and Molecular Biology, 2023)
Elevated plasma MicroRNA-155 (miR-155) levels are strongly associated with cardiac fibrosis and chronic inflammation processes. However, the relationship between miR-155 and paroxysmal atrial fibrillation (PAF) recurrence following cryoablation remains poorly explored. We aimed to evaluate whether elevated miR-155 is related to long-term AF recurrence following cryoablation. Preoperative miR-155 levels were determined in PAF patients undergoing initial cryoablation. Multivariate-adjusted Cox models were constructed to determine the relationship between miR-155 levels and PAF recurrence. Multivariate logistic regression analyses were performed to determine predictors of PAF recurrence. Of the 66 enrolled patients, 13 patients (19.7%) had recurrence at the 12-month following-up. These patients had significantly higher baseline miR-155 levels than those without PAF recurrence ((AAA ± BBB) vs. (AAA ± BBB), P < 0.05). The study results showed that miR-155 expression levels were significantly higher in the experimental group than in the control group. Additionally, logistic regression analysis revealed that miR-155 expression was positively correlated with PAF recurrence after cryoablation. Elevated preoperative miR-155 levels are related to a higher risk of AF recurrence and can independently predict AF recurrence following cryoablation.